2017
DOI: 10.1007/s12035-017-0714-0
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Conditioned Medium from Human Adipose-Derived Mesenchymal Stem Cells is Impaired by N-acetyl Cysteine Supplementation

Abstract: Oxidative stress is a common feature in neurodegenerative diseases associated with neuroinflammation, and therefore, has been proposed as a key target for novel therapies for these diseases. Recently, adipose-derived stem cell (ASC)-based cell therapy has emerged as a novel strategy for neuroprotection. In this study, we evaluate the therapeutic role of ASC-conditioned medium (ASC-CM) against HO-induced neurotoxicity in a new in vitro model of ec23/brain-derived neurotrophic factor (BDNF)-differentiated human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…Recent reports have suggested that therapeutic effects of stem cells are due to factors such as cytokines, microRNAs, and exosomes, which are secreted by stem cells ( Kay et al, 2017 ; Li et al, 2018 ; Palomares et al, 2018 ). The AdMSCs expressing inducible protein-10 (IP-10) reduce melanoma tumor growth and lung metastasis ( Mirzaei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that therapeutic effects of stem cells are due to factors such as cytokines, microRNAs, and exosomes, which are secreted by stem cells ( Kay et al, 2017 ; Li et al, 2018 ; Palomares et al, 2018 ). The AdMSCs expressing inducible protein-10 (IP-10) reduce melanoma tumor growth and lung metastasis ( Mirzaei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…To induce neurotoxicity, Palomares et al [164] used an in vitro model of ec23/brain-derived neurotrophic factor (BDNF)-differentiated human SH-SY5Y neuron-like cells (SH-SY5Yd) exposed to H 2 O 2 . The effect of conditioned medium from human AD-MSCs was neuroprotective; indeed, stressed SH-SY5Y cells recovered normal axonal, electrophysiological features, and cell viability.…”
Section: Mesenchymal Stem Cells Contrast Neuronal Cell Damage Inducedmentioning
confidence: 99%
“…A recent study has demonstrated that the BDNF upregulated the axonal growth in CNS [205]. Besides, the ASC-CM mitigated the oxidative stress in stressed SH-SY5Y neuron-like cells and restored cell morphology, viability, and electrophysiological activity [206]. This restructuring activity was linked with the presence of antioxidant and growth factors, like BDNF, glial cell line-derived neurotrophic factor, and TGF-β1.…”
Section: Asc Secretome and Its Therapeutic Effectmentioning
confidence: 99%